Cigarette Smoke Suppresses the Surface Expression of c-kit and FcεRI on Mast Cells - M. E. Givi; B. R. Blokhuis; C. A. Da Silva; I. Adcock; J. Garssen; G. Folkerts; F. A. Redegeld; E. Mortaz (Mediators of Inflammation)
Chronic obstructive pulmonary disease (COPD) is a multicomponent disease characterized by emphysema and/or chronic bronchitis. COPD is mostly associated with cigarette smoking. Cigarette smoke contains over 4,700 chemical compounds, including free radicals and LPS (a Toll-Like Receptor 4 agonist) at concentrations which may contribute to the pathogenesis of diseases like COPD. We have previously shown that short-term exposure to cigarette smoke medium (CSM) can stimulate several inflammatory cells via TLR4 and that CSM reduces the degranulation of bone-marrow-derived mast cells (BMMCs). In the current study, the effect of CSM on mast cells maturation and function was investigated. Coculturing of BMMC with CSM during the development of bone marrow progenitor cells suppressed the granularity and the surface expression of c-kit and FcεRI receptors. Stimulation with IgE/antigen resulted in decreased degranulation and release of Th1 and Th2 cytokines. The effects of CSM exposure could not be mimicked by the addition of LPS to the culture medium. In conclusion, this study shows that CSM may affect mast cell development and subsequent response to allergic activation in a TLR4-independent manner.